Melatonin Ameliorates MI-Induced Cardiac Remodeling and Apoptosis through a JNK/p53-Dependent Mechanism in Diabetes Mellitus. (9th January 2020) - Lu, Linhe; Ma, Jipeng; Sun, Mingming; Wang, Xiaowu; Gao, Erhe; Lu, Lintao; Ren, Jun; Yang, Lifang; Yang, Jian
Abstract : Diabetes mellitus, a worldwide health threat, is considered an independent risk factor for cardiovascular diseases. The overall cardiovascular risk of diabetes is similar to the one having one myocardial infarction (MI) attack although the precise impact of diabetes on MI-induced myocardial anomalies remains elusive. Given that mortality following MI is much greater in diabetic patients compared to nondiabetic patients, this study was designed to examine the effect of melatonin on MI injury-induced myocardial dysfunction in diabetes. Adult mice were made diabetic using high-fat feeding and streptozotocin (100 mg/kg body weight) prior to MI and were treated with melatonin (50 mg/kg/d, p.o.) for 4 weeks prior to assessment of cardiac geometry and function. The MI procedure in diabetes displayed overt changes in cardiac geometry (chamber dilation and interstitial fibrosis) and functional anomalies (reduced fractional shortening and cardiomyocyte contractile capacity) in association with elevated c-Jun N-terminal kinase (JNK) phosphorylation and p53 level. Melatonin treatment markedly attenuated cardiac dysfunction and myocardial fibrosis in post-MI diabetic mice. Furthermore, melatonin decreased JNK phosphorylation, reduced p53 levels, and suppressed apoptosis in hearts from the post-MI diabetic group. In vitro findings revealed that melatonin effectively counteracted high-glucose/high fat-hypoxia-induced cardiomyocyte apoptosis and contractile dysfunction through a JNK-mediated mechanism, the effects of which were impaired by the JNK activator anisomycin. In summary, our study suggests that melatonin protects against myocardial injury in post-MI mice with diabetes, which offers a new therapeutic strategy for the management of MI-induced cardiac injury in diabetes.